2009
DOI: 10.1021/cm8019445
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State 13C NMR Characterization of Carbon-Modified TiO2

Abstract: Abstract13C-modified TiO2 was prepared to facilitate study of the dopant atoms and trace their chemical fate throughout the process. In the preannealed material, NMR showed strong evidence of many Ti−O−C bonds. After annealing, surface-bound coke is a major component. NMR also showed that a washing step before annealing led to the generation of orthocarbonate (C(OR)4) centers, observed at 126 ppm, which are located deep inside the TiO2 particles. Both NMR and XPS confirmed the presence of small amounts of regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 77 publications
(148 reference statements)
4
43
0
Order By: Relevance
“…3a and b). The C 1s spectrum shows a single strong peak at 284.6 eV and a weak shoulder at around 288.5 eV, which are attributed to the presence of adventitious elemental carbon and C-O bond, respectively [42][43][44]. Generally, the C-O band at 288.5 eV has been considered as the formation of Ti-O-C bond due to the substitution of carbon for some of the lattice titanium atoms, though this peak may come from the surface functional group of carbon black [41][42][43].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3a and b). The C 1s spectrum shows a single strong peak at 284.6 eV and a weak shoulder at around 288.5 eV, which are attributed to the presence of adventitious elemental carbon and C-O bond, respectively [42][43][44]. Generally, the C-O band at 288.5 eV has been considered as the formation of Ti-O-C bond due to the substitution of carbon for some of the lattice titanium atoms, though this peak may come from the surface functional group of carbon black [41][42][43].…”
Section: Resultsmentioning
confidence: 99%
“…The peak at around 281.0 eV of Ti-C bond was not observed in these samples, which suggests that carbon did not substitute for oxygen atom in the lattice of TiO 2 in the current system. It has been reported that the carbon doping states and species cannot be directly confirmed by only analyzing the XPS C 1s spectra [42,44]. Further analysis of the XPS Ti 2p spectra can help to investigate the carbon doping state, because carbon-doping can lead to the formation of oxygen vacancies and Ti 3+ defects and result in a slight shift of the Ti 2p peaks toward the lower binding energy [42][43][44].…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the C-O bond has been considered as the formation of Ti-O-C bond due to carbon doping, though this peak may come from the surface functional group of the AC. [42][43][44][45] Besides the C-C bond, there are two peaks for sample A (see Fig. S3 in the ESI †), though it is not active under visible-light irradiation.…”
Section: Textural Characterizationmentioning
confidence: 99%
“…Hence, carbon doping cannot be directly confirmed by only analyzing the XPS C 1s spectra. 45 Carbon-doping accompanies the formation of oxygen vacancies and Ti 3+ defects, resulting in slight shifts of the Ti 2p peak toward the lower binding energy. [42][43][44][45] Hence, the red shifts of the Ti 2p peak in comparison with undoped TiO 2 are used to highlight the successful carbondoping into the TiO 2 lattice.…”
Section: Textural Characterizationmentioning
confidence: 99%
“…The main ingredient of cotton fiber is cellulose, a linear polymer of D-glucose with 3 hydroxyl groups on C-2, C-3 and C-6 in the 6-member cycle chain. These polar groups can adsorb the nanoparticles via oxygen bonding [1]. However, the carboxylic group is more polar than the hydroxyl one, as well it has a stronger interaction with the hydroxylic group on the nanoparticle surface [2,3].…”
Section: Introductionmentioning
confidence: 99%